A novel frost-free control strategy and its energy evaluation of the CO2 heat pump system. (25th January 2022) - Wang, Anci; Yin, Xiang; Fang, Jianmin; Jia, Fan; Song, Yulong; Cao, Feng
Highlights: A novel frost-free control strategy was proposed and validated. Frosting performance under different control strategies were compared and analysed. Dynamic thermal performance under the frost prone condition was studied. Comprehensive heating capacity and energy efficiency during frosting was evaluated. The optimal control strategy was recommended for different application. Abstract: To solve the problem of severe performance degradation for heat pumps in electric vehicles caused by frosting, a novel frost-free control strategy was proposed and validated. Furthermore, the frosting characteristic of a transcritical CO2 electric vehicle heat pump under different control strategies was investigated. The objective was to provide recommendations for the control logic of heat pumps during actual driving process through evaluating the energy performance with different control strategies. To evaluate the performance under frost process quantitatively, the average energy efficiency and variation rate of heating capacity, COP and operating time were compared. Moreover, the average energy efficiency with PTC auxiliary heater was studied. Then the optimal control strategy was recommended according to the operating time in actual driving conditions. The frost-free control strategy was the best choice when the running time exceeded 60 min, while the constant heating capacity control strategy was the best choice when the running time was within 60 min. The conclusions provided a reference for the development of the automatic frost-free control logic for heat pumps. The proposed frost-free control logic is applicable to different types of heat pumps, and it provides a novel idea for frost-free heating during practical engineering.